The Effect of Administering Vitamin D Supplement on Blood Glucose Level in Gestasional Diabetes Mellitus Rats - Meka Melani Sari; Nuzulia Irawati; Dr. Efrida (Institute of Computer Science (IOCS), 2020)
Gestational Diabetes Mellitus (DMG) occurs due to insulin resistance during pregnancy which causes glucose intolerance in various levels and hyperglycemia. The incidence of DMG in the world and in Indonesia continues to increase every year. Gestational diabetes mellitus can cause complications to the mother and the fetus both during pregnancy and after delivery. Administering vitamin D supplement can reduce blood glucose level and keep the fetal growth rate in normal limits. This study aimed to determine the effect of administering vitamin D supplement on glucose level and fetal growth rate in DMG rats. This is an experimental study with post-test only control group design in 15 pregnant rats with gestational diabetes. Samples were divided into three groups, one control group and two treatment groups which were given vitamin D supplements at a dose of 9µg/kgBW and 18µg/kgBW for 14 days. Blood glucose level examination was done by using a glucometer and the fetal growth rate was done by using an analytical balance and millimeter paper. Statistical testwas conducted by using One Way ANOVA, the significance was determined if p <0.05. Mean ± SD blood glucose levels (mg/dL) in the the control group (170.80 ± 4.147), P1 group (126.00 ± 1.581), P2 group (123.80 ± 1.924) (p 0.001). Statistically there was a significant difference in the administration of vitamin D supplements on blood glucose levels and there was no significant difference in fetal growth rates in DMG rats. The conclusion of this research is that effect administration of vitamin D supplements on blood glucose levels and it does not affect fetal growth rates in DMG rats.